(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
This article examines the narrative voice of La noche de los tiempos, a novel by Antonio Muñoz Molina, according to a communicative model that treats syntactic, semantic, and pragmatics aspects that shed light on the meaning of the text. From a pragmatic perspective I analyze the purpose of the narrative as a communicative act which establishes a relationship of the discourse to its context and of the narrator to the narratee. The choice of narrative voice and its focalization is one of the great achievements of this novel, since it is the source of the work’s verisimilitude and ethical character.